THE PALEOPROTEROZOIC IMANDRA-VARZUGA RIFTING STRUCTURE (KOLA PENINSULA): INTRUSIVE MAGMATISM AND MINERAGENY - V. V. Chashchin; F. P. Mitrofanov (Геодинамика и тектонофизика)
The article provides data on the structure of the Paleoproterozoic intercontinental Imandra-Varzuga rifting structure (IVS) and compositions of intrusive formations typical of the early stage of the IVS development and associated mineral resources. IVS is located in the central part of the Kola region. Its length is about 350 km, and its width varies from 10 km at the flanks to 50 km in the central part. IVS contains an association of the sedimentary-volcanic, intrusive and dyke complexes. It is a part of a large igneous Paleoproterozoic province of the Fennoscandian Shield spreading for a huge area (about 1 million km2), which probably reflects the settings of the head part of the mantle plume. Two age groups of layered intrusions were associated with the initial stage of the IVS development. The layered intrusions of the Fedorovo-Pansky and Monchegorsk complexes (about 2.50 Ga) are confined to the northern flank and the western closure of IVS, while intrusions of the Imandra complex (about 2.45 Ga) are located at the southern flank of IVS. Intrusions of older complexes are composed of rock series from dunite to gabbro and anorthosites (Monchegorsk complex) and from orthopyroxenite to gabbro and anorthosites (Fedorovo-Pansky complex). Some intrusions of this complexes reveal features of multiphase ones. The younger Imandra complex intrusions (about 2.45 Ga) are stratified from orthopyroxenite to ferrogabbro. Their important feature is comagmatical connection with volcanites. All the intrusive complexes have the boninite-like mantle origin enriched by lithophyle components. Rocks of these two complexеs with different age have specific geochemical characteristics. In the rocks of the Monchegorsk and Fedorovo-Pansky complexes, the accumulation of REE clearly depends on the basicity of the rocks, the spectrum of REE is non-fractionated and ‘flat’, and the Eu positive anomaly is slightly manifested. In the rocks of the Imandra complex, the level of REE accumulation is relatively higher. The spectrum of REE here differs with more fractionated LREE with a ‘flat’ distribution of HREE and distinct Eu anomalies. Rocks of all the intrusive complexes are characterized mostly by negative eNd(T) values, and eNd values are distributed more heterogeneously in the rocks of the Monchegorsk complex than in the rocks of the Fedorovo-Pansky complex. Deposits and occurrences of Cr, complex PGE-Cu-Ni and low-sulfide Pt-Pd ores of the world class are spatially related and genetically associated with the IVS intrusive complexes. The Sopcheozero deposit (Monchepluton of the Monchegorsk complex) and Bolshaya Varaka deposit (the same-name intrusion of the Imandra complex) represent a layered Cr mineralization. Complex PGE-Cu-Ni deposits are confined to Monchepluton. They occur in vein ores of the Nittis-Kumuzhya-Travyanaya massifs (which have been worked out) and Sopcha, vein PGE-Cu, injecting Ni ores mostly and bottom deposits of the Nittis-Kumuzhya-Travyanaya massifs, as well as in the Nyud ‘critical’ horizon. In the past 10–15 years, low-sulphide Pt-Pd ores were discovered as new for the Kola region. Two main types of such ores have been distinguished: (1) stratiform (rift) ores being consistent with the massifs’ layering, and (2) basal ores located within lower marginal zones. Deposits of Kievey (West-Pansky massif of the Fedorovo-Pansky complex), horizon 330 of the Sopcha and Vurechuayvench (Monchepluton of the Monchegorsk complex) belong to the first type; the second type is represented by the Fedorovotundrovskoe (Fedorovo-Pansky complex), South Sopcha and Loypishnyun (Monchetundrovsky massif of Monchegorsk complex) deposits.